Detection of the EGFR G719S Mutation in Non-small Cell Lung Cancer Using Droplet Digital PCR - Esteva-Socias, Margalida; Enver-Sumaya, Mónica; Gómez-Bellvert, Cristina; Guillot, Mónica; Azkárate, Aitor; Marsé, Raquel; Sastre, Úrsula; Blasco, Ana; Calabuig-Fariñas, Silvia; Asensio, Víctor José; Terrasa, Josefa; Obrador-Hevia, Antònia (Frontiers in Medicine, 2020)
Objectives: The main objectives of the study were 1) to set-up a droplet digital PCR (ddPCR) assay for the non-invasive detection of G719S EGFR mutation in NSCLC patients; 2) to determine the limits of detection of the ddPCR assay for G719S mutation and 3) to compare COBAS® and ddPCR System for G719S quantification in plasma. Methodology: Plasma ctDNA from 22 NSCLC patients was extracted with the Qiagen Circulating Nucleic Acids kit and quantified by QuantiFluor® dsDNA System. EGFR testing was carried out by digital droplet PCR (ddPCR) with specific probes and primers. Results: We observed the lowest percentage of G719S mutant allele could be detected in a wildtype background was 0,058%. In the specificity analysis, low levels of G719S mutation were detected in healthy volunteers with a peak of 21.65 mutant copies per millilitre of plasma and 6.35 MAFs. In those patients whose tissue biopsy was positive for G719S mutation, mutant alleles could also be detected in plasma using both ddPCR and COBAS® System. Finally, when mutational status was studied using both genotyping techniques, higher mutant copies/ml and higher mutant allele fraction (MAF) correlated with higher Semiquantitative Index obtained by COBAS®. Conclusions: Although tissue biopsies cannot be replaced due to the large amount of information they provide, liquid biopsy and ddPCR represents a new promising strategy for genetic analysis of tumors from plasma samples. In the present study, G719S mutation was detected in a highly sensitive manner, allowing its monitorization with a non-invasive technique.